Development of Interactive Reading Multimedia Based on Educational Games for Grade I Students of Inpres Malakaya Elementary School, Gowa District - Aliem Bahri; Febrianti; Encik Savira Isnah; M. Kharis (Future Science, 2024)
The development of interactive reading multimedia based on educational games for grade I students of SD Inpres Malakaya is motivated by students' issues, such as difficulty distinguishing similar letters and challenges in reading fluency and word formation. Teachers still rely on thematic books for teaching reading, which may lack student interest. This issue is exacerbated by the COVID-19 pandemic, preventing teachers from conducting direct guidance. This research is a Research and Development (R&D) study using the modified 4D model, encompassing three stages: define, design, and develop. The instruments include questionnaires for media and subject matter experts to assess product validity, and for students and teachers to evaluate product feasibility. Validation results by media experts yielded an overall score of 66, with a percentage of 88%, categorized as